Management and Patterns of Field Tennis Sports Development at the PTPM Club (Manado Student Tennis Association) at PELTI Manado City - Apriano Saerang; Merry Julia Jamilah Langi; Thofan Rame (Budapest International Research and Critics University, 2022)
The problem in this researchis the low achievement of junior/student tennis athletes in Manado City, North Sulawesi Province. To improve athlete achievement, it is necessary to have good management and sports coaching patterns at the PTPM (Manado Student Tennis Association) club. The management and pattern of sports coaching is the coordination of all existing resources, including, Human Resources (HR), materials, technology and finance, which are needed by an organization to achieve its goals. In sports management, all resources are pooled to make work and workforce run more productively. The method used is descriptive, namely to collect information about the research subject and behavior similar to the researchto get a general picture of the object to be studied.The percentage data analysis technique is and the research was carried out in September 2021. With a sample of 25 people consisting of coaches who also act as administrators, athletes and parents. The management and pattern of field tennis coaching at the PTPM (Manado Student Tennis Association) club in Manado City, North Sulawesi Province has been going well. Although there are still some things that need to be completed, improved and improved in order to further improve the achievements of junior tennis athletes in Manado City, North Sulawesi Province.